Organic / inorganic hybrid sodium ion battery positive electrode and preparation method thereof
By organically combining MXene with organic quinone materials, an organic/inorganic hybrid sodium ion battery positive electrode is solved, and the low capacity utilization rate of inorganic electrode materials in sodium ion batteries and poor conductivity of organic quinone materials is achieved, and a high performance and high energy density battery positive electrode material is achieved.
Patent Information
- Application Number
- CN202210538877.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-05-18
AI Technical Summary
The inorganic electrode materials of sodium ion batteries have limited their commercial application due to the large radius of sodium ions, which are difficult to effectively apply in sodium ion batteries.
By organically combining MXene with organic quinone material, an organic/inorganic hybrid sodium ion battery positive electrode is formed, and the high conductivity and mechanical properties of MXene are used to make up for the shortcomings of organic quinone electrode materials.
The high conductivity, mechanical and electrochemical performance of the positive electrode material of sodium ion battery is achieved, the overall performance and energy density of the battery are improved, and the assembly cost and time are reduced.
Smart Images

Figure HDA0003649619890000011 
Figure HDA0003649619890000012 
Figure HDA0003649619890000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery preparation, and relates to an organic / inorganic hybrid sodium ion battery positive electrode and a preparation method thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Compared with lithium-ion batteries, sodium-ion batteries have two major advantages: one is that the cost of raw materials is low and they are abundant in resources such as seawater; the other is that sodium-ion batteries have relatively stable electrochemical properties and are safer to use than lithium-ion batteries. However, the radius of sodium ions is large, and it is more difficult to embed and extract them from the lattice of inorganic electrode materials, resulting in low capacity utilization and slow kinetics for these electrode materials, which limits the commercial application of sodium-ion batteries. The organic quinone materials in the electrode materials have large gaps and can reversibly store sodium ions using their own functional groups. Organic quinone materials have high theoretical specific capacity, high redox potential and good electrochemical properties, and have great application potential. However, organic quinone electrode materials have poor conductivity and high solubility in electrolytes, facing challenges in practical applications. Summary of the invention
[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide an organic / inorganic hybrid sodium ion battery positive electrode and a preparation method thereof. The organic / inorganic hybrid sodium ion battery positive electrode organically combines MXene with an organic quinone material to complement their advantages and disadvantages, and the obtained positive electrode material has good conductivity and mechanical properties, and has excellent electrochemical properties.
[0005] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0006] In a first aspect, the present invention provides an organic / inorganic hybrid sodium ion battery positive electrode, wherein the organic / inorganic hybrid sodium ion battery positive electrode is formed by stacking layered MXene nanosheets, and an organic quinone material is uniformly distributed on the surface of the MXene layer or in the MXene nanosheet layer.
[0007] Furthermore, the organic quinone material is selected from one of the organic substances of disodium rose palmitate (Na2C6O6), pentacene tetraketone (PT), tetrahydroxybenzoquinone (THBQ), dichlorodicyanobenzoquinone (DDQ), 2,5-dihydroxy-1,4-benzoquinone (DHBQ), phenanthrenequinone (PhQ), and anthraquinone (AQ).
[0008] In a second aspect, the present invention provides a method for preparing the organic / inorganic hybrid sodium ion battery positive electrode, comprising the following steps:
[0009] The organic quinone powder and the MXene colloidal solution are stirred evenly, and the anti-solvent is mixed with the solution using an anti-solvent method. After stirring at room temperature, the mixture is vacuum filtered and dried to obtain the organic / inorganic hybrid sodium ion battery positive electrode.
[0010] Compared with traditional inorganic materials, organic quinone materials have larger voids and can reversibly store sodium ions using their own functional groups. They also have higher theoretical specific capacity, higher redox potential and better electrochemical performance, and have great application potential. However, organic quinone electrode materials have poor conductivity and high solubility in electrolytes, which poses challenges in practical applications. The MXene in the present invention has good conductivity and adhesion, and can be combined with organic quinone materials to make up for the shortcomings of organic quinone electrode materials.
[0011] The beneficial effects of the present invention are as follows:
[0012] (1) The present invention adjusts the traditional sodium battery positive electrode material, and the composite of organic quinone materials and MXene makes the organic / inorganic hybrid sodium ion battery positive electrode have good electrochemical properties and good mechanical properties and film-forming properties. The flexible MXene / organic composite positive electrode material does not require additives and conductive agents, saving the material cost and time of assembling the battery.
[0013] (2) The high conductivity of flexible MXene improves the overall conductivity of the electrode sheet, and the mechanical properties of MXene are very excellent, providing a good carrier for the loading of high specific capacity active materials and promoting Na + transmission.
[0014] (3) The rich functional groups and large interlayer spacing on the MXene surface can be used to prevent the dissolution of organic quinones in the electrolyte, thereby maintaining its high reversible capacity and achieving its high energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The drawings in the specification, which constitute a part of the present application, are used to provide further understanding of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute improper limitations on the present application.
[0016] Figure 1 This is a physical picture of the flexible MXene / Na2C6O6 composite film prepared in Example 1 of the present invention.
[0017] Figure 2 This is the XRD pattern of the flexible MXene / / Na2C6O6 composite film prepared in Example 1 of the present invention.
[0018] Figure 3 This is a SEM image of the flexible MXene / / Na2C6O6 composite film prepared in Example 1 of the present invention.
[0019] Figure 4 This is a test chart of the cycle performance of a 2032-type button battery using the flexible MXene / / Na2C6O6 composite film of the present invention as the positive electrode material. DETAILED DESCRIPTION
[0020] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0021] In a first aspect, the present invention provides an organic / inorganic hybrid sodium ion battery positive electrode, wherein the organic / inorganic hybrid sodium ion battery positive electrode is formed by stacking layered MXene nanosheets, and the organic quinone material is uniformly distributed on the surface of the MXene layer or in the MXene nanosheet layer.
[0022] Furthermore, the MXene colloidal solution is selected from Ti3C2, Ti2C, V2C, Nb2C, (V 0.5 Cr 0.5 )3C2, V4C3, Nb2C, Nb4C3, Ti3CN, Ti3C2, Ti2C, Ta4C3, Mo2C, TiNbC or Ti3CN, or a mixture of two or more thereof, preferably Ti2C3;
[0023] Furthermore, the organic quinone material is selected from one of the organic substances selected from disodium rose palmitate (Na2C6O6), pentacene tetraketone (PT), tetrahydroxybenzoquinone (THBQ), dichlorodicyanobenzoquinone (DDQ), 2,5-dihydroxy-1,4-benzoquinone (DHBQ), phenanthrenequinone (PhQ), and anthraquinone (AQ), preferably Na2C6O6.
[0024] In a second aspect, the present invention provides a method for preparing the organic / inorganic hybrid sodium ion battery positive electrode, comprising the following steps:
[0025] The organic quinone powder and the MXene colloidal solution are stirred evenly, and the anti-solvent is mixed with the solution using the anti-solvent method, and vacuum filtered and dried to obtain an organic / inorganic hybrid sodium ion battery positive electrode. After cutting, it is directly used as a positive electrode material.
[0026] In some embodiments, the selected anti-solvent is one of ethanol, dichloromethane, cyclohexane, methyl acetate, ethyl acetate, and propyl acetate, preferably ethanol;
[0027] In some embodiments, the volume ratio of the antisolvent to the MXene colloidal solution is 10:1;
[0028] Furthermore, the preparation step of the MXene colloidal solution includes: dissolving the MAX phase powder in a mixed solution of hydrochloric acid and fluoride, peeling off the MXene, and separating to obtain a few-layer or multi-layer MXene colloidal solution;
[0029] More specifically, the preparation steps of the MXene colloidal solution are generally to stir the MAX phase powder in a mixed solution of hydrochloric acid and fluoride, then add water and centrifuge to remove excess acid and fluoride, then add a dispersant, manually peel and centrifuge to separate the obtained few-layer or multi-layer MXene colloidal solution;
[0030] Further, the concentration of MXene colloid solution is 1 g / L-1.5 g / L;
[0031] Further, when the organic quinone powder and the MXene colloid solution are uniformly stirred, the amount of the MXene colloid solution is 10 mL-20 mL, preferably 15 mL;
[0032] Further, the mass of the organic quinone powder is 4 mg-10 mg, preferably 7.5 mg;
[0033] Furthermore, the MXene / organic mixed solution obtained above was filtered by vacuum filtration to form a film, and then dried in a vacuum drying oven at 50° for 12 hours to obtain a sodium battery MXene / organic positive electrode composite membrane material.
[0034] The above organic / inorganic hybrid sodium ion battery positive electrode is cut and directly used as the positive electrode material of the sodium battery. In some embodiments, the electrolyte selected for the sodium battery is one of 1.0MNaPF6 (EC:EMC=1:1, 5% FEC) and 1.0MNaPF6 (100% DIGLYME).
[0035] The excellent theoretical specific capacity of organic quinone electrode materials makes them valuable as positive electrode materials for sodium ion batteries. However, there are many defects in organic quinone electrode materials as positive electrode materials for sodium ion batteries. For example, the actual specific capacity of Na2C6O6 electrode material is much smaller than the theoretical specific capacity of the charge and discharge cycle. The reason is the irreversible phase change and material crushing in the electrochemical cycle. At the same time, the poor conductivity of organic quinone electrode materials themselves and their dissolution problems in electrolytes also limit their application in sodium ion batteries. MXene has the characteristics of high conductivity, low electron diffusion energy barrier and excellent mechanical properties. It can provide a good carrier for the loading of high specific capacity active materials and promote Na +Transport. Studies have shown that sodium ions have little resistance to deintercalation / intercalation between MXene layers, and the volume of MXene hardly expands after sodium ion intercalation. The rich functional groups on the surface of MXene and the large interlayer spacing prevent the dissolution of organic matter in the electrolyte, thus maintaining its high reversible capacity.
[0036] This paper obtains a flexible MXene / organic composite membrane through the anti-solvent method and vacuum filtration method, which can be directly used as the positive electrode material of the sodium battery without the need for a conductive agent or a binder, saving the material cost and time of assembling the battery. This invention can prevent the dissolution of organic matter and increase the conductivity of organic matter without the need for complex organic synthesis or material modification, thereby improving the reversible specific capacity of organic materials and the practicality of sodium batteries.
[0037] The present invention adopts the anti-solvent method, combining the main solvent with the anti-solvent, thereby reducing the solubility of the to-be-crystallized material in the solvent. Organic quinone electrode materials such as Na2C6O6 are slightly soluble in water, and the anti-solvent is added to reduce the solubility of Na2C6O6 in water, so that it can be better composited with MXene during the filtration process.
[0038] The present invention adopts a vacuum filtration method, which has the following advantages: 1. The vacuum filtration method enables the MXene colloidal solution to become a MXene film, and the MXene film has high conductivity and very excellent mechanical properties. 2. During the vacuum filtration process, the organic quinone electrode material and MXene can produce a strong interface contact, so that the organic quinone material is evenly distributed on the surface of the MXene layer or in the MXene nanosheet layer.
[0039] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0040] Example 1
[0041] Take 0.5g Ti3AlC2 powder, put it into a mixed solution of 0.5g LiF and 10mL 6M hydrochloric acid, add 2.5mL water, stir for 24h, centrifuge and wash to remove acid and other impurities to pH 7, then add deionized water to disperse, shake vigorously by hand and centrifuge to obtain a few-layer MXene colloidal solution. Take 7.5mg disodium rose palm acid powder and add it to 15mL MXene colloidal solution, then mix it with ethanol in a volume ratio of 1:10 (150mL) and stir at room temperature for 1h. Subsequently, vacuum filter it using a mixed cellulose membrane and dry it at 50°C for 12 hours to obtain a flexible MXene@Na2C6O6 composite membrane. The obtained film is cut into discs with a diameter of 10mm using a punching machine for assembling batteries.
[0042] The above-synthesized MXene@Na2C6O6 composite film positive electrode material and 1.0MNaPF6 (100% DIGLYME) electrolyte, glass fiber separator, metal sodium sheet, gasket, and battery positive and negative electrode shells are stacked and assembled, and then sealed to assemble into a 2032-type button battery.
[0043] Figure 1 The actual picture of the flexible MXene / Na2C6O6 composite film prepared in Example 1 is shown, indicating the successful preparation of the flexible MXene / Na2C6O6 film and its mechanical properties.
[0044] Figure 2 The XRD pattern of the flexible MXene / Na2C6O6 composite film prepared in Example 1 is shown, indicating the successful preparation of the flexible MXene / Na2C6O6 film.
[0045] Figure 3 The SEM image of the flexible MXene / Na2C6O6 composite film prepared in Example 1 is shown, indicating that Na2C6O6 is dispersed on the MXene surface and in the interlayer gaps.
[0046] Figure 4 The cycling performance test of 2032-type button cell with flexible MXene / Na2C6O6 composite film as cathode material (current density of 200mAg -1 ), it can be seen from the figure that the battery prepared in this embodiment still has a discharge specific capacity of 235mAh / g after 50 cycles, achieving a high energy density.
[0047] Example 2
[0048] Take 0.5g Ti3AlC2 powder, put it into a mixed solution of 0.5g LiF and 10mL 6M hydrochloric acid, add 2.5mL water, stir for 24h, centrifuge and wash to remove acid and other impurities to pH 7, then add deionized water to disperse, shake vigorously by hand and centrifuge to obtain a few-layer MXene colloidal solution. Take 10mg disodium rose palm acid powder and add it to 15mL MXene colloidal solution, then mix it with ethanol in a volume ratio of 1:10 (150mL) and stir at room temperature for 1h. Subsequently, vacuum filter it using a mixed cellulose membrane and dry it at 50°C for 12 hours to obtain a flexible MXene@Na2C6O6 composite membrane. The obtained film is cut into discs with a diameter of 10mm using a punching machine for assembling batteries.
[0049] The above-synthesized MXene@Na2C6O6 composite film positive electrode material and 1.0MNaPF6 (100% DIGLYME) electrolyte, glass fiber separator, metal sodium sheet, gasket, and battery positive and negative electrode shells are stacked and assembled, and then sealed to assemble into a 2032-type button battery.
[0050] Example 3
[0051] Take 0.5g Ti3AlC2 powder, put it into a mixed solution of 0.5g LiF and 10mL 6M hydrochloric acid, add 2.5mL water, stir for 24h, centrifuge and wash to remove acid and other impurities to pH 7, then add deionized water to disperse, shake vigorously by hand and centrifuge to obtain a few-layer MXene colloidal solution. Take 7.5mg Na2C6O6 powder and add it to 10mL MXene colloidal solution, then mix it with ethanol at a volume ratio of 1:10 (100mL) and stir at room temperature for 1h. Subsequently, vacuum filter it using a mixed cellulose membrane and dry it at 50°C for 12 hours to obtain a flexible MXene@Na2C6O6 composite membrane. The obtained film is cut into discs with a diameter of 10mm using a punching machine for assembling batteries.
[0052] The above-synthesized MXene@Na2C6O6 composite film positive electrode material and 1.0MNaPF6 (100% DIGLYME) electrolyte, glass fiber separator, metal sodium sheet, gasket, and battery positive and negative electrode shells are stacked and assembled, and then sealed to assemble into a 2032-type button battery.
[0053] Example 4
[0054] Take 0.5g Ti3AlC2 powder, put it into a mixed solution of 0.5g LiF and 10mL 6M hydrochloric acid, add 2.5mL water, stir for 24h, centrifuge and wash to remove acid and other impurities to pH 7, then add deionized water to disperse, shake vigorously by hand and centrifuge to obtain a few-layer MXene colloidal solution. Take 7.5mg Na2C6O6 powder and add it to 20mL MXene colloidal solution, then mix it with ethanol in a volume ratio of 1:10 (200mL) and stir at room temperature for 1h. Subsequently, vacuum filter it using a mixed cellulose membrane and dry it at 50°C for 12 hours to obtain a flexible MXene@Na2C6O6 composite membrane. The obtained film is cut into discs with a diameter of 10mm using a punching machine for assembling batteries.
[0055] The above-synthesized MXene@Na2C6O6 composite film positive electrode material, 1.0MNaPF6 (100% DIGLYME), glass fiber separator, metal sodium sheet, gasket, and battery positive and negative electrode shells are stacked and assembled, and then sealed to assemble into a 2032-type button battery.
[0056] Example 5
[0057] Take 0.5g Ti3AlC2 powder, put it into a mixed solution of 0.5g LiF and 10mL 6M hydrochloric acid, add 2.5mL water, stir for 24h, centrifuge and wash to remove acid and other impurities to pH 7, then add deionized water to disperse, shake vigorously by hand and centrifuge to obtain a few-layer MXene colloidal solution. Take 7.5mg disodium rose palm acid powder and add it to 15mL MXene colloidal solution, then mix it with ethanol in a volume ratio of 1:10 (150mL) and stir at room temperature for 1h. Subsequently, vacuum filter it using a mixed cellulose membrane and dry it at 50°C for 12 hours to obtain a flexible MXene@Na2C6O6 composite membrane. The obtained film is cut into discs with a diameter of 10mm using a punching machine for assembling batteries.
[0058] The above-synthesized MXene@Na2C6O6 composite film positive electrode material and 1.0MNaPF6 (EC:EMC=1:1, 5% FEC) electrolyte, glass fiber separator, metal sodium sheet, gasket, and battery positive and negative electrode shells are stacked and assembled, and then sealed to assemble into a 2032-type button battery.
[0059] Example 6
[0060] Take 0.5g Ti3AlC2 powder, put it into a mixed solution of 0.5g LiF and 10mL 6M hydrochloric acid, add 2.5mL water, stir for 24h, centrifuge and wash to remove acid and other impurities to pH 7, then add deionized water to disperse, shake vigorously by hand and centrifuge to obtain a few-layer MXene colloidal solution. Take 10mg disodium rose palm acid powder and add it to 15mL MXene colloidal solution, then mix it with ethanol in a volume ratio of 1:10 (150mL) and stir at room temperature for 1h. Subsequently, vacuum filter it using a mixed cellulose membrane and dry it at 50°C for 12 hours to obtain a flexible MXene@Na2C6O6 composite membrane. The obtained film is cut into discs with a diameter of 10mm using a punching machine for assembling batteries.
[0061] The above-synthesized MXene@Na2C6O6 composite film positive electrode material and 1.0MNaPF6 (EC:EMC=1:1, 5% FEC) electrolyte, glass fiber separator, metal sodium sheet, gasket, and battery positive and negative electrode shells are stacked and assembled, and then sealed to assemble into a 2032-type button battery.
[0062] Example 7
[0063] Take 0.5g Ti3AlC2 powder, put it into a mixed solution of 0.5g LiF and 10mL 6M hydrochloric acid, add 2.5mL water, stir for 24h, centrifuge and wash to remove acid and other impurities to pH 7, then add deionized water to disperse, shake vigorously by hand and centrifuge to obtain a few-layer MXene colloidal solution. Take 7.5mg Na2C6O6 powder and add it to 10mL MXene colloidal solution, then mix it with ethanol at a volume ratio of 1:10 (100mL) and stir at room temperature for 1h. Subsequently, vacuum filter it using a mixed cellulose membrane and dry it at 50°C for 12 hours to obtain a flexible MXene@Na2C6O6 composite membrane. The obtained film is cut into discs with a diameter of 10mm using a punching machine for assembling batteries.
[0064] The above-synthesized MXene@Na2C6O6 composite film positive electrode material and 1.0MNaPF6 (EC:EMC=1:1, 5% FEC) electrolyte, glass fiber separator, metal sodium sheet, gasket, and battery positive and negative electrode shells are stacked and assembled, and then sealed to assemble into a 2032-type button battery.
[0065] Example 8
[0066] Take 0.5g Ti3AlC2 powder, put it into a mixed solution of 0.5g LiF and 10mL 6M hydrochloric acid, add 2.5mL water, stir for 24h, centrifuge and wash to remove acid and other impurities to pH 7, then add deionized water to disperse, shake vigorously by hand and centrifuge to obtain a few-layer MXene colloidal solution. Take 7.5mg Na2C6O6 powder and add it to 20mL MXene colloidal solution, then mix it with ethanol in a volume ratio of 1:10 (200mL) and stir at room temperature for 1h. Subsequently, vacuum filter it using a mixed cellulose membrane and dry it at 50°C for 12 hours to obtain a flexible MXene@Na2C6O6 composite membrane. The obtained film is cut into discs with a diameter of 10mm using a punching machine for assembling batteries.
[0067] The above-synthesized MXene@Na2C6O6 composite film positive electrode material and 1.0MNaPF6 (EC:EMC=1:1, 5% FEC) electrolyte, glass fiber separator, metal sodium sheet, gasket, and battery positive and negative electrode shells are stacked and assembled, and then sealed to assemble into a 2032-type button battery.
[0068] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing an organic / inorganic hybrid sodium ion battery positive electrode, characterized in that: The positive electrode of the organic / inorganic hybrid sodium-ion battery is made of stacked layered MXene nanosheets, and the organic quinone material is evenly distributed on the surface of the MXene layer or in the MXene nanosheet layer; The steps include: The organic quinone powder and the MXene colloidal solution are stirred evenly, and the anti-solvent is mixed with the solution using an anti-solvent method, and vacuum filtered and dried to obtain an organic / inorganic hybrid sodium ion battery positive electrode; The layered MXene nanosheets are selected from Ti3C2, Ti2C, V2C, Nb2C, (V 0.5 Cr 0.5 )3C2, V4C3, Nb2C, Nb4C3, Ti3CN, Ta4C3, Mo2C, TiNbC or Ti3CN, or a mixture of two or more thereof; The organic quinone material is selected from one of the organic substances including disodium rosinase Na2C6O6, pentacene tetraketone PT, tetrahydroxybenzoquinone THBQ, dichlorodicyanobenzoquinone DDQ, 2,5-dihydroxy-1,4-benzoquinone DHBQ, phenanthrenequinone PhQ and anthraquinone AQ; The volume ratio of antisolvent to MXene colloidal solution was 10:1; The concentration of the MXene colloid solution is 1 g / L-1.5 g / L; The dosage of MXene colloid solution is 10mL-20mL; the dosage of organic quinone powder is 4mg-10mg; The vacuum filtration and drying specifically comprises: using a vacuum filtration method to filter and form a film, and drying in a vacuum drying oven at 50° C. for 12 hours to obtain an organic / inorganic hybrid sodium ion battery positive electrode; The preparation steps of the MXene colloidal solution include: dissolving MXene phase powder in a mixed solution of hydrochloric acid and fluoride, peeling off the MXene, and separating to obtain a few-layer or multi-layer MXene colloidal solution.
2. The method for preparing the positive electrode of the organic / inorganic hybrid sodium ion battery according to claim 1, characterized in that: The layered MXene nanosheet is Ti3C2.
3. The method for preparing the positive electrode of the organic / inorganic hybrid sodium ion battery according to claim 1, characterized in that: The organic quinone material is Na2C6O6.
4. The preparation method according to claim 1, characterized in that: The selected anti-solvent is one of ethanol, dichloromethane, cyclohexane, methyl acetate, ethyl acetate, and propyl acetate.
5. The preparation method according to claim 4, characterized in that: The antisolvent chosen was ethanol.
6. The preparation method according to claim 1, characterized in that: The amount of MXene colloid solution used is 15 mL; the amount of organic quinone powder used is 7.5 mg.
Citation Information
Patent Citations
Preparation method and application of high-density HATN@MXene flexible self-supporting film electrode
CN113839001A